inggris - Arief Hidayat Afendi; Ratna Endang Widuatie; Titih Nursugiharti; Agus Yulianto; Al-Amin Al-Amin (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
KH Hasyim Asy'ari underlined the significance of instruction as a implies to construct devout and national mindfulness. He accepted that instruction ought to be able to deliver people who are not as it were learned people cleverly, but moreover have tall ethical and otherworldly astuteness. Joining conventional values within the innovative approach to instruction requires alterations to the educational programs and instructing strategies. Techno-Islamic Instructional method underlines the utilize of innovation to bolster student-centred learning, whereas keeping up Islamic values.Qualitative-literature study methodology is a research approach that emphasises in-depth analysis of relevant literature in a field of research. The results Adjusting KH Hasyim Asy'ari's bequest into Techno-Islamic Instructional method is an imperative step in progressing the quality of Islamic instruction within the present day time. By coordination technology and Islamic values, we will make an instruction framework that's not as it were scholastically compelling but too shapes the character of understudies with respectable character